Summary and future development of marine target surveillance based on spatial information network - You HE; Libo YAO; Zhengjie JIANG (Tongxin xuebao)
The space information network is indispensable for marine target surveillance.Multi-satellite information fusion methods which are based on spatial computing mode can improve the ability of wide-area scanning,accurate recognition,persistent tracking and rapid responding.The mode of on-board information fusion for sea target surveillance needs to be further studied.Firstly,the developments of spatial information network and satellite for sea surveillance were discussed and the existing problems were summarized.Then the architecture of marine target surveillance based on spatial computing was put forward.The key technology and future development of on-board computing for ocean target surveillance were studied and discussed in the fields of spatial networking and information fusion.